PENINGKATAN CAPACITY BUILDING DALAM MENDUKUNG INOVASI USAHA KELOMPOK PENGRAJIN ROTAN MAROANGIN - Anita Suardi; Dg. Maklassa; Sitti Marhumi; Sitti Nurbaya (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2023)
This study aims to describe the increase in capacity building in supporting business innovation as well as the driving and inhibiting factors for increasing capacity building in supporting the business innovation of the Maroangin Indah rattan craftsmen group in Pangkep Regency. This type of research is descriptive qualitative data obtained through interviews, observation and documentation. Data were collected from 5 informants through a purposive sampling technique and analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that the training provided by the government is not evenly distributed. However, this is an ongoing program so it is possible to provide training to all craftsmen. Weaving is a basic craftsman skill. Talent and potential need to collaborate to create ideas for innovation. Competency development requires business management training and price agreements. In the formation of a Maroangin Indah certificate in Pangkep Regency, the role of the product development section was a solution in creating various innovations, providing capital assistance in equipment, participating in demonstration activities, craft exhibitions, and comparative studies. The government also plans to build a showroom as a center for rattan crafts to display artisans' handicraft products. Increased capacity building which is reflected in the development of abilities, skills, potential, talents, competency development and solutions in supporting the business innovations of the Maroangin Indah rattan craftsmen group in Pangkep Regency. The driving factors are training, customer requests and business competition while the inhibiting factors are capital, interest and age.